Thermal and hydraulic analysis of a novel double-pipe geothermal heat exchanger with a controlled fractured zone at the well bottom - Agson-Gani, P.H. (Elsevier Ltd, 2022)
This study introduces a novel concept of semi closed-loop double-pipe heat exchangers with a controlled fractured zone at the well bottom to improve the geothermal heat extraction. The proposed model is benefitted from the reliable design of a double-pipe and the higher heat extraction rate of open geothermal systems. A conjugate mathematical model is developed and validated to simulate geothermal heat extraction, while the fractured zone is calculated by implementing the fractal theory. The results suggest that the proposed model can significantly improve the heat extraction rate and thermal power by up to more than 90, with an additional 28 of pumping power. Several operating parameters of the fractured zone are also evaluated, indicating that the increase of the heat extraction rate compared to the closed-loop model was within the range of 48â144 based on its design. Overall, this novel design shows the potential to improve the thermal and hydraulic performances of the conventional closed-loop geothermal system. Â© 2022